The “Second Hit” of Repair in a Rabbit Model of Chronic Rotator Cuff Tear - Wu, Isabella T.; Gibbons, Michael C.; Esparza, Mary C.; Vasquez-Bolanos, Laura S.; Hyman, Sydnee A.; Dorn, Shanelle N.; Singh, Anshuman; Lane, John G.; Fithian, Donald C.; Ruoss, Severin; Ward, Samuel R. (Frontiers in Physiology, 2022)
The rabbit supraspinatus is a useful translational model for rotator cuff (RC) repair because it recapitulates muscle atrophy and fat accumulation observed in humans after a chronic tear (the “first hit”). However, a timeline of RC tissue response after repair, especially with regard to recent evidence of muscle degeneration and lack of regeneration, is currently unavailable. Thus, the purpose of this study was to characterize the progression of muscle and fat changes over time after the repair of a chronic RC tear in the rabbit model. Two rounds of experiments were conducted in 2017–2018 and 2019–2020 with N = 18 and 16 skeletally mature New Zealand White rabbits, respectively. Animals underwent left supraspinatus tenotomy with repair 8 weeks later. The unoperated right shoulder served as control. The rabbits were sacrificed at 1-, 2-, 4-, and 8-weeks post-repair for histological and biochemical analysis. Atrophy, measured by fiber cross-sectional area and muscle mass, was greatest around 2 weeks after repair. Active muscle degeneration peaked at the same time, involving 8% of slide areas. There was no significant regeneration at any timepoint. Fat accumulation and fibrosis were significantly increased across all time points compared to contralateral. Statement of Clinical Significance: These results demonstrate model reproducibility and a “second hit” phenomenon of repair-induced muscle atrophy and degeneration which partially recovers after a short time, while increased fat and fibrosis persist.